General Elections 15 Oct 2019 Final Report - Hanlon, Joseph; Cortez, Edson; Nhancale, Sheila; Mendonça, Magda; Bande, Aldemiro; Nhacume, Nelia; Mahiquene, Telma (Centro de Integridade Pública (Public Integrity Centre), 2020)
Frelimo and President Filipe Nyusi swept away the opposition in the 15 October 2019 general elections, matching Armando Guebuza's 2009 landslide. But there were widespead reports of misconduct. On a 52% turnout, Nyusi won 73% of the vote with over 50% in all provinces. Frelimo won majorities in all provincial parliaments and in the first ever election of governors, Frelimo won all ten.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; electoral geography / geografia eleitoral

Republic of Mozambique: Final Report General and Provincial Assembly Elections - European Union Election Observation Missionn (European Union Election Observation Mission, 2019)
On 15 October, Mozambicans elected the president, members of the Assembly of the Republic, members of the 10 provincial assemblies, and 10 provincial governors. Although there was a considerable number of participants, including recently registered political parties, the electoral process was dominated by the three main parties: the ruling Mozambican Liberation Front (FRELIMO), the main opposition Mozambican National Resistance (RENAMO), and the Mozambican Democratic Movement (MDM)
Keywords: G - Mozambique / Moçambique; L - english / inglês; electoral geography / geografia eleitoral

Elite Bargains and Political Deals Project: Mozambique Case Study - Vines, Alex (UK Government Stabilisation Unit, 2018)
This case study is one of a series commissioned to support the Stabilisation Unit’s (SU) development of an evidence base relating to elite bargains and political deals. The project explores how national and international interventions have and have not been effective in fostering and sustaining political deals and elite bargains; and whether or not these political deals and elite bargains have helped reduce violence, increased local, regional and national stability and contributed to the strengthening of the relevant political settlement. Drawing on the case studies, the SU has developed a series of summary papers that bring together the project’s key findings and will underpin the revision of the existing ‘UK Approach to Stabilisation’ (2014) paper. The project also contributes to the SU’s growing engagement and expertise in this area and provides a comprehensive analytical resource for those inside and outside government
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; conflict - civil war / conflito - guerra civil; conflict / conflito; decentralization / descentralização; electoral geography / geografia eleitoral